Cell‐Repellent Interfaces: Micropatterned Cell‐Repellent Interface Using Femtosecond Laser Direct Writing to Engineer Controlled Cell Organization (Adv. Mater. Technol. 7/2021). Issue 7 (5th July 2021) - Yang, Wenguang; Chu, Honghui; Cai, Shuxiang; Liang, Wenfeng; Yu, Haibo; Wang, Yuechao; Liu, Lianqing
Abstract : W. G. Yang, Haibo Yu, Lianqing Liu, and co‐workers demonstrate a flexible and practical method to construct cell‐repellent interfaces and engineer controlled cell organization is investigated in article number 2100178 . Microcraters patterns have been rapidly fabricated using femtosecond laser direct writing, and shown outstanding superhydrophobicity. Furthermore, cell adhesion is inhibited by the features and arbitrary cell patterns are achieved by selective cell adhesion induced by distribution of microcraters structures.